Comparison of Fentanyl and Clonidine for Attenuation of the Haemodynamic Response to Laryngocopy and Endotracheal Intubation - Sameenakousar, (JCDR Research and Publications (P) Limited, 2013)
Introduction: Laryngoscopy and tracheal intubation after the induction of anaesthesia, are nearly always associated with sympathetic hyperactivity. To ‘blunt’ this pressor response, various methods have been tried, but very few studies have been done to assess the effects of fentanyl orI.V. clonidine on the haemodynamic response during laryngoscopy and tracheal intubation. The purpose of this study was to compare these agents, to find the drug which was best suited for this purpose and the most favourable time for its administration. Methods: This was a prospective study which involved 3 groups of patients. The patients in group-1 (control) were given normal saline and the groups 2 and 3 were given i.v. fentanyl and clonidine respectively. Each group had 50 patients who presented for elective, non-cardiovascular surgeries. All the patients were ASA-1 or ASA-II and were operated in PESIMSR, Kuppam. Results: The heart rate rise was 48.07% in the control group, whereas it was significantly lower in the fentanyl (II) 27.75% and the clonidine groups (III) 12.57% (p<0.001). In the control group, the systolic blood pressure increased maximally after 5 minutes (42.62%) i.e., immediately after the laryngoscopy and the intubation. It decreased gradually over 10 minutes (17.39%). With the administration of fentanyl, the maximum increase as compared to the preinduction value was 9.91%, but it was only 7.38% in the clonidine group. Both, when they were compared with the control, showed a significant suppression (P<.001), with clonidine showing better results. The maximum increase in the diastolic blood pressure was 30.12% in the control group (P<.001) at 5 min and it was 18.22%, and 6.15% in the fentanyl and the clonidine groups respectively, with clonidine faring better again (P<.001). Interpretation and Conclusion: Clonidine showed better attenuation of the sympathetic response, which is statistically highly significant and it remained so till the end of 10 minutes. Intravenous clonidine 2;g/kg which is administered 5 minutes before the laryngoscopy can be recommended to attenuate the sympathetic response to the laryngoscopy and the intubation.